Nutritional evaluation of non-conventional feed resources from wasteland and its effect on yield, chemical composition and inter-relationship between constituents of goat milk - KOUSHKI, M R; GUPTA, M P; OGRA, J L (The Indian Journal of Animal Sciences, 2013)
All non-conventional forages evaluated in the present study were palatable to goats. The control feed had higher crude protein, energy, ether extract and calcium while the non-convenuonal forages contained a higher per cent of crude fibre, nitrogen-free extract and ash. The digestibility of nutrients except that of other extract was higher on non-conventional forage feeding than on control. Leucaena leucocephala possessed highest nutritive value among non-convcntional forages, and its nutritive value was about similar to that of control feed. Under various feeding regimens, milk yield was significantly (p<0.01) higher in Jamunapari goats than in Barbari goats. Breed variation significantly influenced the total solids, fat, chloride and emergy contents of goat milk. Various feeding regimens, had however, insignificant effect on these values. The titratable acidity, lactose, SNF and ash were neither affected by breed variation nor variation in feeding regimens. Inter relationship between different conntituents of goat milk remained unaltered by feeding regimens but breed variation had significant (P<0.01) effect on Koestler number, SNF/TS and protein/fat ratios.